Analisis Faktor-Faktor Yang Mempengaruhi Komitmen Kerja Karyawan Studi Pada Karyawan Batik Brotoseno Sragen - Mulyaningsih, Mulyaningsih, Drs. Sri Padmantyo, MBA (2016)
The purpose of this study were: 1) Determine whether the variable of transformasional leadership, motivation, work environment, work ethics and competence affect employee commitment. 2) Determine which of the employee commitment consists of variables transformasional leadership, motivation, work environment, work ethics and competence the most dominant influence. The population in this study were all employees Brotoseno Batik Sragen, while samples in this study were 90 respondents. The sampling technique by using random sampling. The analytical method used is: 1) Questionnaire testing techniques, the validity and reliability testing, 2) Test analysis covering multiple linear regression test 3). Test hypothesis of the t test and F test. The results of data analysis showed that: 1) Test instruments, all questionnaires declared valid and reliable. 2) test results of data analysis showed that a) Results of t test showed that the motivation of the variables have the most influence on employee commitment this is indicated by the significance value of less than 0.005. b) F test results showed variable transformasional leadership, motivation, work environment and work ethics organizational together influential signifiakan the employee commitment in Brotoseno batik Sragen, this is shown by the significant value of less than 0.005.